Approaches for Improvement of Livestock Production System as affected by Climate Change in Dry Lands - Patil, N V; Pathak, K ML (Annals of Arid Zone, 2016)
In the arid and semi-arid regions, the livestock husbandry is playing pivotal role in the economic sustenance and employment generation, but is also suffering due to recurrent droughts and other unfavorable conditions of climate, soil and water, which also adversely affect the crop husbandry. Despite higher animal number and significant contribution to the livestock production at national and regional levels, the low productivity remains a matter of concern. The low and non-productive animals need to be curbed in number as these contribute to climate change and global warming. There is a need for effective conservation and improvement of native breeds, stop uncontrolled animal breeding, which results in loss of precious genetic material due to prevalent extensive rearing and transhumance practice followed in the region in search of food. There is also need appropriate feed security measures to address the issues of degradation of grazing resources, which need protection and rejuvenation and also policy support for creation of feed, fodder banks and complete feeds like CFBs and TMRs to take care of productivity improvement. The issues of management of livestock, nutritional measures to reduce methane emission from enteric digestion and also management of health under changing climate need proper consideration as new emerging and re-emerging diseases of livestock in the region have an adverse effect on livestock productivity. The value addition to the marketable animals and their produce need an extensive support of the government to provide real benefit to the poverty stricken small, marginal and landless labourer section of the rural society who have livestock rearing as the main activity and which thrive well despite the threats from climate change issues. Key words: Ruminants, sheep, goat, camel, methane, climate change